1988
DOI: 10.1177/030089168807400315
|View full text |Cite
|
Sign up to set email alerts
|

Palmar-Plantar Erythrodysesthesia Syndrome Associated with Short-Term Continuous Infusion (5 Days) of 5-Fluorouracil

Abstract: A case of palmar-plantar erythrodysesthesia syndrome (PPES) observed during a 120-h infusion of 5-fluorouracil (5-FU) is presented. This syndrome has been described in the literature after protracted infusion chemotherapy of over 30 days. The agent most frequently associated with this syndrome was 5-FU. A 53-year-old man was admitted to the hospital with a well-differentiated squamous cell carcinoma of the retromolar trigone. The patient received 100 mg/m2 of cisplatin on day 1 and 120-h continuous infusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…These symptoms would appear on the soles or the palms or sometimes on neck or chest or extremeties (Baack and Burgdorf, 1991). It is also reported that HFS is dose dependent and the probable mechanism is due to the accumulation of the drug in the skin (Bellmunt et al, 1988). HFS is associated with increase in number of eccrine glands on the palm and the soles, which are prone to cytotoxicity if the drug or its metabolite is bio-available in the sweat (Mrozek-Orlowski et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…These symptoms would appear on the soles or the palms or sometimes on neck or chest or extremeties (Baack and Burgdorf, 1991). It is also reported that HFS is dose dependent and the probable mechanism is due to the accumulation of the drug in the skin (Bellmunt et al, 1988). HFS is associated with increase in number of eccrine glands on the palm and the soles, which are prone to cytotoxicity if the drug or its metabolite is bio-available in the sweat (Mrozek-Orlowski et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Concerning 5-FU, PPES was initially reported mostly in patients treated with continuous or protracted infusion of this drug, but has also been observed after 5-FU i.v. bolus injection (3,4,8). As shown in Table 1, the frequency of PPES in patients treated with 5-FU given in bolus form can be as high as 27%, clearly indicating that the likelihood of such a reaction to 5-FU bolus administration is greater than is usually thought.…”
mentioning
confidence: 94%
“…PPES is a reaction characterized by tenderness, swelling and erythema of palmar and plantar surfaces that has been reported in association with 5-FU administration (3)(4)(5)(6). PPES tends to resolve a few days after 5-FU discontinuation but frequently recurs when therapy is reinstituted; oral administration of pyridoxine has been recommended as a treatment that allows continuation of chemotherapy with 5-FU while maintaining remission of this cutaneous complication (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that a complex mechanism is responsible for the induction of this condition. We report here three cases of chemotherapy- (3,5,20,25,30,31) Peculiar acral erythema (2) Distinctive acral erythema (10) Chemotherapy-induced acral erythema (18,23,24,29) Painful red hands (21) Erythema and desquamation (4) Palmar-plantar erythema (11,12) Palmar-plantar erythrodysesthesia (7,13,14,15,22,27,28) Toxic erythema of palms and soles (19) Erythematous eruption ofthe palms and soles (1) Dermatitis of the hands and feet (9) Hand-foot syndrome (8,26) Burgdorf's reaction (24) induced acral erythema.…”
Section: Introductionmentioning
confidence: 99%